Desain Sistem Informasi Klinik Pratama Mirah Medika - Salsabila Shofiyah (Bandung Conference Series: Accountancy, 2022)
Abstract. Pratama Mirah Medika Clinic is one of the service companies engaged in health services by providing various polyclinic services such as general polyclinics, dental polyclinics, pediatric polyclinics, and obgyn polyclinics and services that support activities in such polys such as pharmaceutical services and laboratory services. The problems contained in The Pratama Mirah Medika Clinic are related to the task trap that occurs in the registration and financial administration, in addition, the data management and storage system is still done manually. The systems and procedures in each part of the polyclinic are inconsistent and there are documents that are not in accordance with standards and some reports are not made by the function of the section in the clinic. The purpose of this research is to create an information system design model for each part of the clinic The importance of computerized systems in the operational activities of the clinic can improve the quality of health services provided by the clinic. To produce a structured system, the method used in this design is FAST (Framework For Application Of System Technique), by following the system development stage, as well as data collection techniques in the form of JAD (Join Application Development) so that it will produce a system that has more structure. The results of the design conducted by the researchers are in the form of recommendations for the design of information systems that can support health services provided by Pratama Mirah Medika Clinic. Abstrak. Klinik Pratama Mirah Medika merupakan salah satu perusahaan jasa yang bergerak dibidang pelayanan kesehatan dengan menyediakan berbagai pelayanan poliklinik seperti poliklinik umum,poliklinik gigi,poliklinik anak,dan poliklinik obgyn dan pelayanan yang mendukung kegiatan pada poli tersebut seperti pelayanan farmasi dan pelayanan laboratorium .Permasalahan yang terdapat pada Klinik Pratama Mirah Medika berkaitan dengan adanya perangkapan tugas yang terjadi pada bagian administrasi pendaftaran dan keuangan, ,selain itu sistem pengelolaan dan penyimpanan data masih dilakukan secara manual.Adapun sistem dan prosedur pada tiap bagian poliklinik yang tidak konsisten serta terdapat dokumen yang tidak sesuai standar dan beberapa laporan tidak dibuatkan oleh fungsi bagian di klinik. Tujuan penelitian ini adalah untuk membuat model perancangan sistem informasi untuk setiap bagian klinik.Pentingnya sistem yang terkomputerisasi pada kegiatan operasional klinik dapat meningkatkan mutu pelayanan kesehatan yang diberikan oleh klinik. Untuk menghasilkan sistem yang terstruktur maka metode yang digunakan pada perancangan ini adalah FAST (Framework For Application Of System Technique), dengan mengikuti tahapan System Development. Serta teknik pengumpulan data berupa JAD (Join Application Development) sehingga akan menghasilkan sistem yang lebih memiliki struktur. Hasil perancangan yang dilakukan oleh peneliti yaitu berupa rekomendasi rancangan sistem informasi yang dapat menunjang pelayanan kesehatan yang diberikan Klinik Pratama Mirah Medika.